Hope [compact disc] - NF (Musician) (NF Real Music, 2023)
The fifth studio album from Billboard chart-topping, multiplatinum rapper, NF. Known for rapping quick-witted lyrics over hip-hop beats and cinematic production, NF has built a loyal fan base that has earned him over 30 billion global streams and established NF as one of the most consumed artists today. This is a 13-track album boasting instant hits, such as Happy; Motto; and notable Grammy-nominated features with singer-songwriter Julia Michaels on Gone and rapper Cordae on Careful.